Diários on-line da cibercultura como espaço de reflexão na formação inicial de professores de pedagogia da Universidade Federal de Sergipe - Oliveira, Arlene Araújo Domingues (2020)
In the early twentieth century, the teacher training course was integrated into universities due to the growth of industrialization in Brazil and the search for greater schooling by education professionals, thus expanding the higher education system. In this research, which aimed to understand how reflections on the initial training, present in the cyberculture online diaries, of the students of the Pedagogy course at the Federal University of Sergipe, Prof. Alberto Carvalho, students in training experienced cyberculture practices by producing reflections on their initial training process, in online interviews. The methodological tracking of this qualitative research, using a research-training method in culture, which allows the learned and implicated researcher to form and be trained with cultural research practitioners. An epistemological approach to data analysis was multi-referential, which presented a plural look at the investigated object. From the interpretation and analysis of the information produced with the research subjects, the following three notions emerged: reflection on training and technologies; mediation with technologies in education; and challenges and dilemmas in the teaching internship. A research designed for an initial training, oriented to the social, political and economic transformations of the 21st century, is important for the digital technologies that are present in the activities of all the subjects of the course curriculum and not only in a single subject, because in this way it makes it is difficult to immerse yourself in culture as reflective and critical practitioners/cultural practitioners/social actors, capable of understanding and transforming the current educational reality into a society that is permeated by technologies.